The Use Of Addie Model In Developing Teaching Materials In Elementary Schools: A Literature Study - Ramlan Mahmud (Sains Global Institut, Indonesia, 2026)
The development of teaching materials in elementary schools is one of the efforts to improve the quality of learning and help students better understand learning content. One of the most widely used models in developing teaching materials is the ADDIE model because it has systematic stages and is easy to apply. This article aims to review the use of the ADDIE model in developing teaching materials in elementary schools through a literature study. The method used is a literature review by collecting various sources such as books, journals, and relevant research findings. The results of the study show that the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation, can help produce more structured teaching materials that are in accordance with the needs of elementary school students. In addition, several studies show that the use of the ADDIE model can increase students’ learning motivation and understanding in the learning process.